Awareness of Chemical Innovations Among Teachers of Chemistry - et. al., Rashwan Jalil Saeed Al-Mashkoor, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify: Awareness of chemical innovations among chemistry teachers. Statistically significant differences in awareness of chemical innovations, according to the gender variable (males, females) and years of service (less than 15 years, more than 15 years). In order to achieve the objectives of the research, the researcher adopted the descriptive research method, and the research community was identified and his sample was selected: Chemistry teachers in middle, middle and high schools affiliated to the General Directorate for Education in Al-Qadisiyah for the academic year (2020-2021) AD, and the research sample consisted of (400) teachers and a school of chemistry and by the fact ( 187) teachers, and (213) female teachers. A measure of awareness of chemical innovations was built and consisted of (54) items. The scale was applied to the research sample, and the results showed poor awareness of chemical innovations among chemistry teachers. The awareness of the chemical innovations was not affected by the variable of sex and years of service. In light of these results, the researcher developed a set of recommendations and proposals.